Pengaruh Lingkungan Sekolah, Fasilitas, dan Layanan Administrasi Terhadap Kepuasan Siswa SMKS Yami Waled Kabupaten Cirebon - Silviani Silviani; Badawi Badawi; Citra Faathir Widiana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
From the standpoint of service marketing management, customer satisfaction plays a significant role in fostering loyalty and a favorable perception of organizations, including educational institutions. As the ones who get educational services, students play a crucial part in evaluating the caliber of school services. The purpose of this study is to examine how student satisfaction at SMKS YAMI Waled, Cirebon Regency, is impacted by the school's surroundings, amenities, and administrative services. Ninety respondents were given questionnaires as part of the study's associative quantitative methodology. Coefficient of determination (R2), t-test, F-test, and multiple linear regression were the data analysis methods employed. The findings demonstrated that, partially and concurrently, the elements of the school environment, facilities, and administrative services had a favorable and significant impact on student satisfaction. The three independent variables considerably contributed to the explanation of changes in student satisfaction, as demonstrated by the coefficient of determination (R2) value of 35.7%. According to these results, maintaining a positive school climate, offering sufficient facilities, and providing effective administrative support are all critical to raising student satisfaction. As a result, schools must put plans into place to raise the standard of instruction in a sustainable and integrated way..